STRATEGI PENINGKATAN KINERJA PERSONEL SANDI KAMAR SANDI INTELIJEN PANGKALAN TNI ANGKATAN UDARA ADI SOEMARMO, SURAKARTA - Yusuf, Ramadhan Ardian; Harnaeni, Nani; Saksono, Lalang (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The preparation of cryptography personnel in the Cryptography Intelligence Room of Adi Soemarmo Air Force Base is crucial for ensuring professional execution of their duties. Leadership plays a vital role in setting policies, while cryptography personnel must maintain high awareness and determination to enhance their capabilities. To achieve optimal performance, human resource improvements are needed in terms of skills, knowledge, and attitude. This research aims to identify the factors causing the suboptimal performance of Cipher Personnel in the Cryptography Intelligence Room of Adi Soemarmo Air Force Base and develop strategies to enhance their effectiveness. A qualitative research method, often referred to as naturalistic inquiry, is used to analyze these issues. The study results indicate that the performance of Cryptography Personnel in handling encryption activities at Adi Soemarmo Air Force Base can be assessed in three key areas. First, their skills are generally good but require further development, particularly in cyber-related cryptographic analysis, which remains suboptimal in execution. Second, their knowledge is strong, as they possess fundamental expertise in encryption, including cipher machine operation, encryption security, and administrative procedures. Lastly, their attitude is largely positive—marked by honesty, responsibility, and openness to feedback. However, some personnel still need improvement in professional demeanor. To enhance performance, continuous training and skill development in cybersecurity and cryptographic analysis are essential. Strengthening knowledge through advanced learning programs and fostering a more disciplined and adaptable mindset among personnel will further optimize their contributions to encryption-related operations.